Tinjauan Yuridis Pembuatan Akta Peralihan Hak Atas Tanah yang Tidak Sesuai dengan Peraturan Perundang-Undangan - Dewanata, Rizky (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the responsibilities of the Land Deed Making Officer in making the deed of transfer of land rights that were not in accordance with the laws and regulations and to analyze the legal consequences of making the deed of transfer of land rights that were not in accordance with the laws and regulations. This study used normative juridical with a statutory approach and a conceptual approach. The responsibility of the Land Deed Making Officer in making the deed of transfer of land rights that were not in accordance with the laws and regulations was imposed in the form of administrative sanctions in the form of a written warning, dishonorable discharge, honorable discharge, or temporary dismissal. The legal consequences of making a deed of transfer of land rights that were not in accordance with statutory regulations are categorized into two, namely civil and administrative legal consequences. The civil legal consequences were related to the validity of the deed of transfer of land rights which is cancelled or can be cancelled by law, while administratively the deed of transfer of land rights that was made contains legal defects.